Maturity Level Analysis of Politap’s Information Technology Governance Using COBIT 2019 Framework - Rizqia Lestika Atimi; Refid Ruhibnur (Universitas Pendidikan Indonesia, 2024)
The implementation of information technology at POLITAP, intensively carried out since 2019, has consumed quite a bit of budget and resources, has a risk of failure, and in the future will become increasingly complex following the growth of the organization. This investment is expected to be directly proportional to the improvement of the organization's business processes and the achievement of organizational goals, thereby providing a competitive advantage for the organization. IT governance is a form of good corporate governance. For this reason, IT governance analysis is an important thing to do in the POLITAP environment. This research aims to analyze the maturity level of the implementation of information technology infrastructure at POLITAP using the COBIT 2019 framework. Maturity level analysis was carried out on the capability level assessment of four domains, namely, EDM, APO, BAI, and DSS. Based on the assessment results, the average capability level of the four domains is at level 1. Therefore, the maturity level of IT governance at POLITAP is at the initial level, which means that the overall goals of the organization have not been focused on being achieved because the IT governance process has not been properly organized. good and complete.